2022
DOI: 10.3389/fpsyg.2022.866270
|View full text |Cite
|
Sign up to set email alerts
|

The Flipped Learning and Blendspace to Improve Pupils’ Speaking Skills

Abstract: During the COVID-19 pandemic, the continuity of teaching and learning is very important to provide sustainable education to all pupils. The most difficult aspect of language acquisition has always been the speaking component. Pupils’ lack of interest and the difficulty in teaching and practicing speaking skills in the traditional classroom are the main issues that hinder pupils’ speaking skills. Thus, the purpose of this study was to explore the flipped learning approach to improve primary school pupils’ speak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…One of the major issues raised by the students is their attitude, which makes them afraid to approach their instructors during interactions with them. Research by Santhanasamy and Yunus, (2022), which supports this finding, showed that English language learners' shyness and nervousness in the language were caused by their inadequate language proficiency. In a similar vein, research by Hussain, Akhtar, Shabir, Aslam, and Arshad (2021)also supported the notion that a lack of vocabulary and language competence causes ESL students' shyness and speaking anxiety.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…One of the major issues raised by the students is their attitude, which makes them afraid to approach their instructors during interactions with them. Research by Santhanasamy and Yunus, (2022), which supports this finding, showed that English language learners' shyness and nervousness in the language were caused by their inadequate language proficiency. In a similar vein, research by Hussain, Akhtar, Shabir, Aslam, and Arshad (2021)also supported the notion that a lack of vocabulary and language competence causes ESL students' shyness and speaking anxiety.…”
Section: Discussionsupporting
confidence: 56%
“…Other challenges in learner-to-instructor interaction related to the learners themselves such as learners' lack of motivation, learners' challenges in using digital tools, and others. Other than that, learners' challenges in learner-to-instructor interaction in blended learning are also related to learners' language anxiety (Santhanasamy & Yunus, 2022). Furthermore, problem in learner-to-instructor interaction also includes a delayed response from the instructors (Paris, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the research conducted, Santhanasamy and Yunus (2022) state that the online flipped classroom teaching approach has proven to be a flexible teaching and learning method that teachers should use to improve student motivation and engagement in learning. Similarly, Linling and Abdullah (2023) find that the flipped classroom can improve student engagement, autonomy, and responsibility for learning, Creative Commons by the Authors is licenced under CC-BY which in the 21 st century is a crucial component for developing students' technological competencies and long-term ambitions and can help students develop responsibility for lifelong learning.…”
Section: Online Flipped Classroommentioning
confidence: 99%
“…Contrastingly, Santhanasamy and Yunus [35] employed a ipped classroom, shifting the lecture paradigm. Students independently delved into materials, reserving classroom sessions for enriching, interactive speaking tasks, thereby amplifying engagement and self-driven motivation.…”
Section: Ielts Speaking Trainingmentioning
confidence: 99%